Wet Pasta “Fettuccine" Jackfruit Seed Flour Substitution: Physical and Organoleptic Quality - Jennifer Angelina; Mariani Mariani; Annis Kandriasari (Jurnal Ilmiah Mandala Education (JIME), 2026)
This study aims to examine the effect of jackfruit seed flour (Artocarpus heterophyllus) substitution on the physical and organoleptic qualities of fresh fettuccine pasta as an alternative to partially replacing wheat flour. The research was conducted using an experimental method with three levels of jackfruit seed flour substitution: 5%, 10%, and 15%. Physical quality tests included water absorption capacity and elasticity, while organoleptic evaluations covered color, aroma, taste, and texture. The results of ANOVA analysis indicated that jackfruit seed flour substitution had no significant effect on water absorption or elasticity. Meanwhile, the Kruskal-Wallis test showed a significant effect on color and aroma, but no significant effect on taste and texture. Based on the Tukey post-hoc test, the 5% substitution level provided the best results in terms of color and aroma. This study suggests that substituting wheat flour with up to 5% jackfruit seed flour can produce fresh fettuccine with good physical and organoleptic quality, and has the potential to become a local food innovation that helps reduce dependency on wheat flour